Primary Small Bowel Melanoma: A Case Report and Review of Literature - Graças, Amanda M.; Souza, Willy P.; Canut, Ana Carolina A.; Franciss, Maurice Y.; Zilberstein, Bruno (Frontiers in Surgery, 2022)
Background: The present study analyzes diagnostic and therapeutic surgical aspects of primary small bowel melanoma, describing a clinical case and reviewing the literature. Malignant melanomas represent 1 to 3% of all malignant tumors of the gastrointestinal tract and are therefore uncommon. Case report: This case report refers to a 55-year-old male patient, complaining of abdominal pain, blackened stools and palpable tumor in the abdomen for approximately thirty days. A tomography scan was performed, which revealed thickening and parietal enhancement of small intestine loops with mesenteric adenomegaly and intermingled collection. For diagnostic confirmation, laparoscopy was performed, which revealed a tumor at the jejunal level, and its resection was performed in the same act. The anatomopathological examination revealed that it was a primary small bowel melanoma. Conclusion: The bibliographic research of small bowel melanoma demonstrated that, in this situation, the lesion can be interpreted as a primary site or metastatic lesion, considering the possibility of a single primary lesion, whose diagnosis becomes more laborious. In such cases, adjuvant therapy must be considered. The expected five-year survival is around 9 to 13%.